Sn‐Based Alloys Synthesized in an Ionic Liquid at Room Temperature: Cu6Sn5 as a Case Study. Issue 4 (25th February 2020) - Soulmi, Nadia; Porras Gutierrez, Ana Gabriela; Rizzi, Cécile; Sirieix‐Plénet, Juliette; Gaillon, Laurent; Groult, Henri; Rollet, Anne‐Laure; Umut, Evrim; Kruk, Danuta; Duttine, Mathieu; Borkiewicz, Olaf. J.; Lebedev, Oleg I.; et al.
Abstract: Sn‐based alloys are increasingly investigated owing to possible electronic/structural modulations of interest for electrocatalysis and energy storage applications. Here, we report on the use of a chemical system consisting of an ionic liquid (1‐ethyl‐3‐ methylimidazolium bis(trifluoromethanesulfonyl)imide: [EMIm + ][TFSI − ]) and Sn‐based precursor Sn(TFSI)2 both featuring similar anionic groups. This strategy increases the solubility of the cationic precursor in the IL and avoids the formation of side‐products during the precipitation of Sn‐nanoparticles formed upon reaction with a reducing agent (NaBH4 ). Using NMR relaxometry, we further established that these nanoparticles are stabilized by specific interactions with the cationic group of the IL. Targeting the composition Cu6 Sn5, we further demonstrated that this approach can be used to prepare Sn‐based alloys which could not be prepared using conventional chloride‐based precursors. Abstract : The use of a chemical system consisting of an ionic liquid (IL: [EMIm + ][TFSI − ]) and metallic precursors based on TFSI − anionic groups enabled the preparation of a Sn‐based alloys which could not be prepared using conventional chloride precursors.